Tree Model for Kadam (Anthocephalus chinensis) Plantations of West Bengal - Singh, S. P. (Indian Forester, 1981)
Tree model to stimulate growth and yield of Kadam has been developed. With its help, it is feasible to predict yields obtainable under different site conditions and different predefined intensity of low (ordinary) thinnings. It thus can provide information to decide initial spacing for planting so as to obtain maximum volume output from the site.